2004
DOI: 10.1089/104454704773660912
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Effect of a 980-nm Diode Laser in the Root Canal Wall Dentin of Bovine Teeth

Abstract: Objective: The aim of this in vitro study was to investigate the antibacterial depth effect of continuous wave laser irradiation with a wavelength of 980 nm in the root canal wall dentin of bovine teeth. Background Data: The long-term success of an endodontic therapy often fails due to remaining bacteria in the root canal or dentin tubules, which cannot be sufficiently eliminated through the classical root canal preparation technique nor through rinsing solutions. Materials and Methods: A total of 102 slices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
122
2
21

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(146 citation statements)
references
References 19 publications
1
122
2
21
Order By: Relevance
“…The results of the present study was in accordance with several studies which reported that complete eradication of bacteria was achieved only through high-power irradiation of diode laser ranges from 0.5-15 W (16) and 980-nm diode laser achieved the maximum bacterial reduction when the amount of power delivered was increased (17) . Moreover, it has been showed that using diode laser with 1.3W output power was more effective in streptococcus mutans reduction compared to diode laser with 1 W output power (11) .…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study was in accordance with several studies which reported that complete eradication of bacteria was achieved only through high-power irradiation of diode laser ranges from 0.5-15 W (16) and 980-nm diode laser achieved the maximum bacterial reduction when the amount of power delivered was increased (17) . Moreover, it has been showed that using diode laser with 1.3W output power was more effective in streptococcus mutans reduction compared to diode laser with 1 W output power (11) .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, efforts are being made to reduce their numbers. This has become a major topic in dental treatment and various methods have been examined [24][25][26] . With further advances in plasma technology together with the recent availability of low-temperature and atmospheric pressure stable equipment, the potential for applications of plasma even in the field of clinical dentistry have been increased.…”
Section: Ros Inhibition Testmentioning
confidence: 99%
“…Further investigations using natural teeth are needed to obtain further evidence of the sterilization effect of the LF jet, before clinical application of this newly developed technology can be attempted. In the past, various methods such as laser, high frequency electrical pulses and iontophoresis have been developed in an attempt to sterilize microorganisms [24][25][26] . The favorable results of the present study therefore indicate that the newly developed LF jet have a great potential for being used in the field of dental treatment.…”
Section: Ros Inhibition Testmentioning
confidence: 99%
“…In fact, the method is mostly limited to a dentin depth between 100 and 300 μm. Deeper dentin tubules house many thousands of remaining bacteria, and these bacteria can migrate into and multiply inside the root canal system [13,14]. Furthermore, the complexity of the root canal system is well known to be one of the major challenges in root canal preparation [6], lateral canals, ramifications, and accessory canals where conventional treatments cannot reach bacteria [6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the conventional method, lasers of suitable wavelengths have an excellent capacity for bacterial reduction at elimination depths exceeding 1000 μm in deep dentin tubules [13,21,22]. However, despite the potential benefits of lasers, too high, a dose of the absorbed energy may cause thermal damage to periodontal ligaments and lad to bone necrosis [15,23,24].…”
Section: Introductionmentioning
confidence: 99%